Pandangan dan Alasan Pelaku terhadap Tindakan Korupsi: Analisis Sosiologis di Lembaga Pemasyarakatan - Ciek Julyanti Hisyam; Hassanah, Anissatul; Bima Ajie Bhagaskara; Fakhri Bima Priyanto; Nelli Putri Widiyati; Nur Al Din Firdos Gamal; Surya Hadi Muharam; Syofa Sasabila; Zahirah Ramadhani (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
.. Corruption is a complex problem in Indonesia that harms the country and undermines public trust. This study uses a qualitative approach with a phenomenological method to understand the views of individuals involved in corruption in correctional institutions. The research shows that corruption is not only considered an individual crime, but is also related to the context of bureaucracy and power. Referring to Michel Foucault’s thinking, corruption is analyzed as part of a network of power and norms in the workplace. The interview results reveal that perpetrators see their actions as administrative errors due to unclear rules and system weaknesses, rather than deliberate acts of corruption. These findings emphasize the importance of viewing corruption as a social phenomenon and the need for improvements in bureaucratic structures and integrity enforcement.